TECHNOLOGY OF ADDITIVE MANUFACTURING: A COMPREHENSIVE REVIEW - Md. Imam Hossain; Md. Sakib Khan; Imrul Kayes Khan; Khan Rajib Hossain; Yanzhao He; Xiaolong Wang (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ, 2024)
The process of additive manufacturing (AM), commonly known as 3D printing, is a method of constructing a component by progressively adding material in layers using digital 3D design information. As part of 'Industry 4.0,' many industrial technologies are rapidly increasing to thrive in the twenty-first century. This study goes over seven different types of additive manufacturing in great detail. These technologies make it possible to make complex, high-value parts quickly and in small quantities without using as much energy or material or making as many tools as subtractive manufacturing does. Besides, AM also possesses some particular challenges, like post-processing, material unavailability, software issues, etc. The application of AM is expanding rapidly from micro to macro-scale sectors. 3D printing technology will change industrial operations in the following years. Eventually, the elected technology will be closely related to the proposed function.